Profil " Orang-orang Pinggiran Amerika" dalam Cerpen-cerpen Umar Kayam - Rakhmat Soleh (Humaniora, 2004)
This paper is a result of research on Umar Kayam's Short Stories which have American background and character. These short stories are very interesting because they are written by the writer who is not American, despite the fact he had lived in the United States for several years. In these short stories, the writer, who is in fact a sociologist, used Seymour Chatman's approach to expose American profile naturally.